Immunity to herpes simplex virus type 2: recurrent lesions are associated with the induction of suppressor cells and soluble suppressor factors. - Iwasaka, T (1983)
Cell-mediated immunity to herpes simplex virus type 2 was investigated in infected inbred strain 13/N guinea pigs with (45%), and without, a history of recurrent herpetic disease (A. D. Donnenberg, E. Chaikof, and L. Aurelian, Infect. Immun. 30:99-109, 1980). Induction of suppressor cells capable of reducing the proliferative response of herpes simplex virus type 2-stimulated immune lymphoid cells was demonstrated in spleen cells from animals with a history of recurrent disease at recrudescence and convalescence but not in spleen cells from quiescent animals or from animals without a history of recurrent herpetic disease (seropositive controls). Suppressor cells were also detected in the peripheral blood but only from three of seven studied animals, and only at recrudescence. In addition to inhibitory cell-cell interactions, the herpes simplex virus type 2-activated regulatory cells of animals with recrudescent herpetic lesions elaborated soluble suppressor factors affecting lymphocyte proliferation. Suppression mediated by suppressor factors was observed only when suppressor factors were added at an early stage of in vitro culture and was reversed by medium exchange throughout the 6 days of culture. Sephadex chromatography revealed the presence of factors capable of differentially modulating the proliferative response of herpes simplex virus-stimulated immune cells and concanavalin A-stimulated normal lymphoid cells.